Toward Choice-Theoretic Foundations for Behavioral Welfare Economics - Bernheim, B. Douglas; Rangel, Antonio (American Economic Review, 2007)
Interest in behavioral economics has grown in recent years, stimulated largely by accumulating evidence that the standard model of consumer decision making provides an inadequate, positive description of human behavior. Behavioral models are increasingly finding their way into policy evaluation, which inevitably involves welfare analysis. No consensus concerning the appropriate standards and criteria for behavioral welfare analysis has emerged yet. This paper summarizes our effort to develop a unified framework for behavioral welfare economics (for a detailed discussion see Bernheim and Rangel 2007) — one that can be viewed as a natural extension of standard welfare economics. Standard welfare analysis is based on choice, not on utility or preferences. In its simplest form, it instructs the planner to respect the choices an individual would make for himself. The guiding normative principle is an extension of the libertarian deference to freedom of choice, which takes the view that it is better to give a person the thing he would choose for himself rather than something that someone else would choose for him. We show that it is possible to extend the standard choice-theoretic approach to welfare analysis to situations where individuals make inconsistent choices, which are prevalent in behavioral economics.